2021
DOI: 10.3390/app11157123
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Global Warming Impact Evaluation of Medium and High Temperature Heat Pumps Using Low GWP Refrigerants

Abstract: This study provides a global warming impact analysis of environmentally friendly refrigerants used as replacements for R134a and R245fa. R290, R1234yf, R1234ze(E), R513A and R450A are considered as refrigerants to replace R134a in medium temperature applications. For R245fa, there are five alternative refrigerants, R1224yd(Z), R600, R1336mzz(Z), R1233zd(E) and R1234ze(Z), which are selected for high-temperature applications. The analysis is done considering the emission factors in Brazil, Sweden, Canada and Po… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2025
2025

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 21 publications
0
2
0
Order By: Relevance
“…In addition, several results on fluids alternative to R410A have been obtained by numerical simulations [20][21][22][23][24][25]. In particular, Yu et al [20] performed a theoretical screening of refrigerant mixtures subjected to a multiparameter optimization process consisting of GWP, flammability and thermodynamic parameters; starting from 12 pure refrigerants, the screening identified several mixtures fulfilling all the restrictions, which were promising to be used in applications with a GWP limit below 150.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, several results on fluids alternative to R410A have been obtained by numerical simulations [20][21][22][23][24][25]. In particular, Yu et al [20] performed a theoretical screening of refrigerant mixtures subjected to a multiparameter optimization process consisting of GWP, flammability and thermodynamic parameters; starting from 12 pure refrigerants, the screening identified several mixtures fulfilling all the restrictions, which were promising to be used in applications with a GWP limit below 150.…”
Section: Introductionmentioning
confidence: 99%
“…In particular, Yu et al [20] performed a theoretical screening of refrigerant mixtures subjected to a multiparameter optimization process consisting of GWP, flammability and thermodynamic parameters; starting from 12 pure refrigerants, the screening identified several mixtures fulfilling all the restrictions, which were promising to be used in applications with a GWP limit below 150. Ghanbarpour et al [21] provided a global-warming impact analysis of environmentally friendly refrigerants used as replacements for R-134a and R-245fa in medium-and high-temperature heat pumps by considering the emission factors of different countries. The results revealed that in addition to the GWP, the emission factor associated with the sources of electricity generation has a crucial impact on indirect emissions determining whether it is beneficial to employ alternative refrigerants in the heat pump systems.…”
Section: Introductionmentioning
confidence: 99%